The reputation of philanthropy since 1750 : Britain and beyond - Cunningham, Hugh (Manchester University Press, 2020)
Most people now associate philanthropy with donations of money by the rich to good causes. It has not always been so. The Reputation of Philanthropy explores how our modern definition came about and asks why praise for philanthropy and philanthropists has always been matched by criticism. Were we really capable of loving all of humankind? Was it possible that what was thought of as philanthropy might create a dependency class and do more harm than good? Was it sensible to focus so much on far away places to the neglect of the poor at home? Deeply researched, timely and accessible, this book will inform today's thinking about the role that philanthropy should play in British society. The criticisms of philanthropy in the past have telling echoes in the present.
Keywords: Charities -- Great Britain -- History.; Dons de charité -- Grande-Bretagne -- Histoire.; HISTORY / Europe / Great Britain; Charities; Great Britain; Benevolence.; Capitalism.; Charity.; Civil Society.; Enlightenment.; Evangelicalism.; National Identity.; Philanthropy.; Political Economy.; Romanticism.; History